For f ( x ) = 4 x + 2 4 x ,
f ( n 1 ) + f ( n 2 ) + f ( n 3 ) + ⋯ + f ( n n − 2 ) + f ( n n − 1 ) = 2 0 1 9
Find n .
This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try
refreshing the page, (b) enabling javascript if it is disabled on your browser and,
finally, (c)
loading the
non-javascript version of this page
. We're sorry about the hassle.
We can rewrite f ( x ) = 1 − 4 x − 1 / 2 + 1 1 , so we have i = 1 ∑ n − 1 ( 1 − 4 i / n − 1 / 2 + 1 1 ) n − 1 − i = 1 ∑ n − 1 4 i / n − 1 / 2 + 1 1 i = 1 ∑ n − 1 4 i / n − 1 / 2 + 1 1 = 2 0 1 9 = 2 0 1 9 = n − 2 0 2 0 Let a i = n i − 2 1 be the exponent of 4 in the above sum. Now the key observation is that a i = − a n − i , and 4 a i + 1 1 + 4 a n − i + 1 1 = 4 a i + 1 1 + 4 − a i + 1 1 = 1 . Using the substitution i ↦ n − i (which runs over the terms of the sum in reverse order), we can write i = 1 ∑ n − 1 4 a i + 1 1 i = 1 ∑ n − 1 4 a n − i + 1 1 = n − 2 0 2 0 = n − 2 0 2 0 and adding these two equations gives i = 1 ∑ n − 1 1 n − 1 n = 2 n − 4 0 4 0 = 2 n − 4 0 4 0 = 4 0 3 9
Problem Loading...
Note Loading...
Set Loading...
For f ( x ) = 4 x + 2 4 x , then
f ( 1 − x ) ⟹ f ( x ) + f ( 1 − x ) = 4 1 − x + 2 4 1 − x = 4 + 2 ( 4 x ) 4 = 2 + 4 x 2 = 4 x + 2 4 x + 2 + 4 x 2 = 1 Multiply up and down by 4 x Divide up and down by 2
Then we have:
f ( n 1 ) + f ( n 2 ) + ⋯ + f ( n n − 2 ) + f ( n n − 1 ) ⟹ f ( n 1 ) + f ( n 2 ) + ⋯ + f ( 1 − n 2 ) + f ( 1 − n 1 ) = 2 0 1 9 = 2 0 1 9
Since f ( n k ) + f ( 1 − n k ) = 1 , there are 2019 f ( n k ) - f ( n n − k ) pairs. That is 4038 f ( ⋅ ) terms or n − 1 = 4 0 3 8 ⟹ n = 4 0 3 9 .